Sleep and Wake Affect Glycogen Content and Turnover at Perisynaptic Astrocytic Processes - Bellesi, Michele; de Vivo, Luisa; Koebe, Samuel; Tononi, Giulio; Cirelli, Chiara (Frontiers in Cellular Neuroscience, 2018)
Astrocytic glycogen represents the only form of glucose storage in the brain, and one of the outcomes of its breakdown is the production of lactate that can be used by neurons as an alternative energetic substrate. Since brain metabolism is higher in wake than in sleep, it was hypothesized that glycogen stores are depleted during wake and replenished during sleep. Furthermore, it was proposed that glycogen depletion leads to the progressive increase in adenosine levels during wake, providing a homeostatic signal that reflects the buildup of sleep pressure. However, previous studies that measured glycogen dynamics across the sleep/wake cycle obtained inconsistent results, and only measured glycogen in whole tissue. Since most energy in the brain is used to sustain synaptic activity, here we employed tridimensional electron microscopy to quantify glycogen content in the astrocytic processes surrounding the synapse. We studied axon-spine synapses in the frontal cortex of young mice after 7h of sleep, 7-8h of spontaneous or forced wake, or 4.5 days of sleep restriction. Relative to sleep, all wake conditions increased the number of glycogen granules around the synapses to a similar extent. However, progressively longer periods of wake were associated with progressively smaller glycogen granules, suggesting increased turnover. Despite the increased number of granules, in all wake conditions the estimated amount of glucose within the granules was lower than in sleep, indicating that sleep may favor glucose storage. Finally, chronic sleep restriction moved glycogen granules closer to the synaptic cleft. Thus, both short and long wake lead to increased glycogen turnover around cortical synapses, whereas sleep promotes glycogen accumulation.